Strategies of National Cultural Centres in Multicultural Cities (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2025)
The article is devoted to a comparative analysis of the strategies of national cultural centres in multicultural cities on the example of Moscow, London and Singapore. The approaches to the promotion of intercultural dialogue, adaptation to the local context and digitalization of cultural activities are considered. Special attention is paid to the challenges: financing, accessibility for marginalised groups and ethical dilemmas of cultural commercialisation.